The Effect of Information, Fear, and Risk Perceptions to Pro-Environmental Behavior among University Students in Indonesia - Fitri, Dyah E Noor; Nastiti, Anindrya (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Climate change is a serious threat to human safety and health. Pro-environmental behavior can avoid more serious risks and harm. Pro-environmental behavior is influenced by information, fear, and risk perceptions. As future educators, planners, and policymakers, it is critical to understand the factors influencing students' pro-environmental behavior. This study, therefore, aims to examine the factors influencing students' pro-environmental behavior based on the Protection Motivation Theory. A 77-item questionnaire was completed by 415 students from the Faculty of Arts and Languages, Science, and Education, randomly selected using the cluster sampling method in their last lecture class. Confirmatory factor analysis and structural equation modeling showed that information, fear, and risk perception (reward, perceived severity, and perceived vulnerability) are both directly and indirectly mediated by motivation. In addition, the research identified the indirect and negligible effects of various protection motivation theory factors, including cost, responseefficacy, and self-efficiency. Further, an unexpected finding determines that pro-environmental behavior was unrelated to demographic and socioeconomic background. Overall, the study's outcomes offer recommendations to socialize the risks climate change better causes to human health and safety, increasing fear and risk perceptions that may improve pro-environmental behavior. Additionally, stricter environmental behavior regulations are needed to penalize polluters and stop rewarding maladaptive behaviors.